The Benefits of Rolling Admission to a University-Based Medical Laboratory Sciences Program. - BEHAN, KRISTINA JACKSON (Clinical Laboratory Science)
The stakeholders of a university-based medical laboratory sciences (MLS) program include students, clinical training sites, and university administration. Each group presents specific challenges to the program. University administrators scrutinize programs with low enrollment for their cost to benefit ratio. Clinical sites are resistant to increasing the number of trainees. Undergraduate and postbaccalaureate students must complete rigorous prerequisites by a specific deadline to apply. To address these issues, the MLS department at University of West Florida undertook rolling admission. Postbaccalaureate biomedical sciences students from the institution have satisfied the program prerequisites and are recruited by email. The postbaccalaureate degree consists of 3 semesters of university-based didactic courses (offered once per year), followed by 2 semesters at a clinical site (offered year-round). Rolling admission increased our average annual enrollment from 13 to 30 students. Most clinical affiliates agreed to extend their training to year-round and accept more trainees when they considered the hiring benefit of 3 waves of graduates per year. This advantage is validated by the 100%job placement of programgraduates within 3--6months. Students in their third semester have increased responsibility relative to the newer students in laboratory activities and also host weekly study sessions. All students benefit from this peer-teaching. Furthermore, it provides an opportunity for leadership for peer-teachers and fosters an interest for training future students at the bench. The recruitment of postbaccalaureate students and the offer of next-semester admission brings in high-quality and prepared applicants. In conclusion, rolling admission has many facets that make it beneficial for the university, the clinical training site, and the students.